47 The impact of supportive-expressive group therapy (SEGT) as an intervention on health-related outcomes and social support for people with advanced disease: a systematic review. Issue 3 (1st September 2018) - Bei, Eva; Kupeli, Nuriye; Candy, Bridget
Abstract : Introduction: SEGT has been found to be a valuable manualised model of therapy for reducing emotional distress facilitating the person's management of the disease-related symptoms and improving quality of life in cancer populations (Butler et al . 2009; Classen et al . 2001; Lemieux et al . 2007). The fundamental domains covered by this model include promoting emotional expression confronting existential issues and optimising social support (Classen et al . 2001; Spiegel Bloom and Yalom 1981). Despite trials there are to our knowledge no systematic reviews that have sought to critic and pool evidence from all Randomised Controlled Trials (RCTs) on SEGT for people with advanced disease. Aims: To critique and pool the evidence from RCTs on the effectiveness of SEGT as a palliative care intervention for patients with advanced disease. Methods: Four databases (Pubmed Medline CINAHL PsycINFO) conference proceedings and grey literature were searched for relevant studies in April 2018. A combination of MeSH and free-text terms on SEGT and end-of-life were used. Key review processes will be undertaken in duplicate. If appropriate meta-analysis will be considered. Results: The search identified unique 2291 citations. Screening these identified 27 potential relevant studies. Following full text review and contact with the authors of not-available full text papers five RCTs on SEGT met our inclusion criteria. Conclusions: This review is at data extraction phase it will be completed by September. Further understanding of the quality of evidence impact of SEGT on health-related outcomes and social support will allow conclusion to be made for clinical practice. References: . Butler LD, Koopman C, Neri E, Giese-Davis J, Palesh O, Thorne-Yocam KA, Dimiceli S, Chen X, Fobair P, Kraemer HC, Spiegel D. Effects of supportive-expressive group therapy on pain in women with metastatic breast cancer. Health Psychology2009;28(5):579–587. . Classen C, Butler LD, Koopman C, Miller E, DiMiceli S, Giese- Davis J, Fobair P, Carlson RW, Kraemer EC, Spiegel D. Supportive-expressive group therapy and distress in patients with metastatic breast cancer: A randomized clinical intervention trial. Archives of General Psychiatry2001;58:494–495. . Lemieux J, Beaton ED, Hogg-Johnson S, Bordeleau JL, Hunter J, Goodwin PJ. Responsiveness to change to change due to supportive-expressive group therapy improvement in mood and disease progression in women with metastatic breast cancer. Qual Life Res2007;16:1007–1017. . Spiegel D, Bloom JR, Yalom I. Group support for patients with metastatic cancer. A randomized outcome study. Archives of General Psychiatry1981;38:527–533.